ANALISIS KESULITAN PEMBELAJARAN MATEMATIKA MENGGUNAKAN METODE DARING DI SMP NEGERI 11 LUBUKLINGGAU - Nanda Riyani; Idul Adha; Efuansyah E. (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the difficulties of learning mathematics using online methods atSMP Negeri 11 Lubuklinggau for the 2020/2021 academic year. This research is a quantitative descriptive type of research. The data collection technique in this study used a questionnaire distributed to students in the form of a link and interviews with a class VIII mathematics teacher at SMP Negeri 11 Lubuklinggau. The results in this study are: 1) Implementation of mathematics learning using the online method using the WhatsApp application, 2) analysis of technical difficulties with a total average of 83.87%; analysis of the implementation of learning a total average of 83.11%; and analysis of the difficulty of external factors with a total average of 85.35%.